PRICING WATER FOR IRRIGATION: A COMPARATIVE STUDY OF CONTINGENCE VALUATION AND DOSE-RESPONSE METHODS - C. Carramaschi, Eduardo; M. Cordeiro Neto, Oscar; M. Nogueira, Jorge (Science & Technology Journals, 2000)
This paper presents results of a study on the demand for water irrigation. We simulate changes in demand due to changes in the price of water. To estimate these prices, two methods were applied for a sample of farmers: the contingence valuation (CVM) and the dose-response (production function, MDR) methods. They were applied on an irrigated agricultural area near by Brasília (Federal District), in the Rocinha River watershed. These farmers have never paid for water irrigation. From a theoretical view-point, CVM estimates reflect the maximum amount an agent is willing to pay for a cubic meter of water. On the other hand, MDR estimates may be interpreted as the maximum an agent is able to pay for the same cubic meter. Assuming a rational behaviour by farmers, one should expect CVM values to be smaller than MDR ones. Our empirical results were coherent with this expectation and with other similar applied studies.